Hearing loss and its link to cognitive impairment and dementia - Azeem, Abdul; Julleekeea, Arun; Knight, Beth; Sohail, Isha; Bruyns-Haylett, Michael; Sastre, Magdalena (Frontiers in Dementia, 2023)
Hearing loss is an important risk factor for the development of dementia, particularly Alzheimer’s disease (AD). Mid-life hearing loss increases the risk of developing dementia by double any other single factor. However, given this strong connection between hearing loss and AD, the mechanisms responsible for this link are still unknown. Data from observational studies relating hearing loss and cognitive impairment, measured with standardised questionnaires, has shown a strong relationship between them. This is similar to findings from animal studies, which show that inducing hearing loss via prolonged loud sound exposure or ear canal blocking, can impair cognitive abilities. Interestingly, studies in humans with age-related hearing impairment provide evidence to suggest there is a rise in phosphorylated tau in the cerebrospinal fluid, but no such relationship has been identified for changes in amyloid-beta. In addition, a lack of social interactions precipitating from hearing loss has been associated with the development of dementia through a supposed reduction in cognitive load and processing requirements. Given this link between hearing loss and dementia, the question arises whether the restoration of hearing might mitigate against the onset or progress of AD. Indeed, there is a growing body of research that suggests that those who wear hearing aids for age-related hearing problems maintain better cognitive function over time than those who do not. These are compelling findings, as they suggest the use of hearing aids has the potential to be a cost-effective treatment for those with hearing loss both prior (for those at high risk for AD) and after the development of symptoms. This review aims to summarise the current theories that relate hearing loss and cognitive decline, present the key findings of animal studies, observational studies and summarise the gaps and limitations that need to be addressed in this topic. Through this, we suggest directions for future studies to tackle the lack of adequately randomised control trials in the field. This omission is responsible for the inability to provide a conclusive verdict on whether to use hearing interventions to target hearing-loss related cognitive decline.